The Mechanism of Insulin-Like Growth Factor II mRNA-Binging Protein 3 Induce Decidualization and Maternal-Fetal Interface Cross Talk by TGF-β1 in Recurrent Spontaneous Abortion - Zhu, Rong-hui; Dai, Fang-fang; Yang, Dong-yong; Liu, Shi-yi; Zheng, Ya-jing; Wu, Ma-li; Deng, Zhi-min; Wang, Zi-tao; Zhang, Yu-wei; Tan, Wei; Li, Zhi-dian; He, Juan; et al. (Frontiers in Cell and Developmental Biology, 2022)
Recurrent spontaneous abortion (RSA) is defined as the loss of two or more consecutive intrauterine pregnancies that are clinically established early in pregnancy. To date, the etiology and underlying mechanisms of RSA remain unclear. It is widely thought that the impair of decidualization is inclined to induce subsequent pregnancy failure and leads to the dysregulation of extra-villous trophoblast invasion and proliferation through maternal-fetal crosstalk. However, the mechanism of decidualization in RSA has yet to be understood. In our study, we demonstrate that decidual samples from RSA patients have significantly higher Insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3) and lower TGF-β1 levels compared to healthy controls. Besides, the overexpression of IGF2BP3 in human endometrial stromal cells (hESCs) can lead to the impair of decidualization in vitro-induced model and the abnormal cell cycle regulation. Furthermore, TGF-β1 and MMP9 levels were greatly increased after decidualization, whereas IGF2BP3 overexpression inhibited endometrial mesenchymal decidualization by downregulating TGF-β1, impeding maternal-fetal interface cytokine cross-talk and limiting the ability of trophoblast invasion. In conclusion, our investigation firstly demonstrates that abnormal elevation of IGF2BP3 in the pregnant endometrium leads to the impair of decidualization and abnormal trophoblast invasion, thereby predisposing individuals to RSA.